Hubungan Antara Perhatian Orangtua terhadap Kegiatan Belajar Siswa dengan Kedisiplinan Siswa di SMP Negeri Parakansalak-Sukabumi - Lisna Sujana; Endin Nasrudin; Suryadi Ahmad (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2021)
The purpose of this study was to determine the attention of parents towards children's learning in Islamic Religious Education subjects at SMP Negeri Parakansalak Sukabumi, and to determine student discipline, as well as to determine the relationship between parents' attention to children's learning in Islamic Religious Education subjects with student discipline. The method in this research is descriptive method. According to Winarno Surakhmad, descriptive investigation is aimed at solving problems that exist in the present, because the problem being researched is a problem to be solved now. From the results of the correlation analysis, it is known that the reality of parents' attention to children's learning activities with the learning discipline of students at SMP Negeri Parakansalak has a high correlation. This fact is based on the calculated value of the correlation coefficient of 0.62. A price of this size is in the interval between 0.60 - 0.80, i.e. it falls on a high qualification. Then from the results of the calculation of the degree of influence of variable X on variable Y proved to be 22%. Thus, there are still around 78% other factors that can affect the learning discipline of students of SMP Negeri Parakansalak, Sukabumi Regency.